Don't get caught flat footed – How over-pronation may just be a dysfunctional model. Issue 2 (April 2015) - Wallden, Matt
Abstract For many years there has been a long-held clinical belief that a flat or over-pronating foot should be supported; yet in every other part of the body it has long been recognised that use of support (if at all) should generally be limited to acute rehabilitation. Why should the foot be any different? To support a biological structure, in the long term, is to weaken it. Panjabi's model of joint stability offers insight into why the idea of arch support, as well-intentioned as it may have been, may be a dysfunctional model. A test (and conditioning exercise) is presented which appears to support the notion that there is no such thing as a flat foot; only a de-conditioned foot.